e EXPERIMENTAL & NUMERICAL STUDY OF BUCKLING BEHAVIOR FOR STAINLESS STEEL 304 ALLOY COLUMNS UNDER DYNAMIC LOADS: abstract, introduction, mathematical and experimental models, results and discussion, conclusions (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
In the present research the effect of corrosion on buckling behavior of 304 stainless steel with increasing of compressive dynamic loads was studied. There are long types of the columns were used. For compression test, there are 24 columns specimens were used in the dynamic axis, 12 columns tests were carried out with increasing in the dynamic axis of compressive load, while for the corrosion test was performed by using 12 specimens were buried for two months under the ground before tested them. The digital gauge was employed at the distance about 0.7 for the column length at the fixed end of column. has alarm system was used to define critical buckling and to avoid the failure of the specimen and installed at the distance equal to 0.7 of the column length from fixed end. The empirical results showed that the effect of negatively corrosion on mechanical properties of alloys with 2.53% reduction of ultimate tensile strength comparing with non-corroded specimens, in the other hand the corrosion will reduce the critical buckling load by 6% for two months. The experimental results comparing with the standard theories of the buckling behavior and with the finite element (ANSYS) results to verify the mathematical model.